2015
DOI: 10.1515/hukin-2015-0069
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Association Between Motor and Anthropometric Variables with Change of Direction Speed and Reactive Agility Performance

Abstract: There is an evident lack of studies examining the factors associated with reactive agility performances. The aim of this study was to evaluate the association between anthropometrics, body composition, jumping capacity, reactive strength, and balance with a stop-and-go change of direction speed (CODS) and reactive agility. The total sample comprised 39 male (body height: 182.95 ± 5.19 cm; body mass: 80.66 ± 7.69 kg) and 34 female (body height: 171.45 ± 6.81 cm; body mass: 61.95 ± 6.70 kg) college-level athlete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 20 publications
3
36
0
7
Order By: Relevance
“…Most specifically, it is reasonable to expect that different sports develop sport-specific agility such as forward-backward running in basketball, zig-zag sprinting agility in soccer, etc., as indirectly confirmed in recent investigations where authors developed sport-specific agility tests for handball, emphasising the crucial movement agility in this sport (i.e. lateral displacement) ( Spasic et al, 2015 ). Therefore, in those studies including athletes from different sports, a relatively low correlation between different agility tests is actually a natural consequence of the development of some sport-specific type of agility ( Metikos et al, 2003 ; Sekulic et al, 2013 ).…”
Section: Discussionmentioning
confidence: 52%
“…Most specifically, it is reasonable to expect that different sports develop sport-specific agility such as forward-backward running in basketball, zig-zag sprinting agility in soccer, etc., as indirectly confirmed in recent investigations where authors developed sport-specific agility tests for handball, emphasising the crucial movement agility in this sport (i.e. lateral displacement) ( Spasic et al, 2015 ). Therefore, in those studies including athletes from different sports, a relatively low correlation between different agility tests is actually a natural consequence of the development of some sport-specific type of agility ( Metikos et al, 2003 ; Sekulic et al, 2013 ).…”
Section: Discussionmentioning
confidence: 52%
“…The significant differences in the CODS and RAG between performance levels are particularly important in light of the previously discussed non-significant differences between performance levels in other conditioning capacities. More precisely, studies conducted to date have regularly confirmed the importance of sprinting and jumping capacities in different CODS performances, whereas the reactive-strength index (RSI) is reported as an important determinant of reactive-agility ( Sekulic et al, 2013 ; Sattler et al, 2015 ). Moreover, it must be noted that U17 and U19 players did not differ in body dimensions (BH and BM) or BF%, which is also noted as an important determinant of CODS in reactive-agility in previous investigations ( Sisic et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…At contact with the ground, they were instructed to shorten the contact time (CT) and maximize the JH as much as possible. The RSI was calculated as JH/CT (m/s) as previously reported, and the highest score was used for the analysis ( Sattler et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, reducing body fat could likely have a positive effect on both reactive strength and futsal-specific agility. Specifically, such influence is suggested for other team sports in which jumping capacities and agility are important determinants of success ( Sattler et al, 2015 ; Sisic et al, 2016 ; Pehar et al, 2018 ). Consequently, a decrease in body fat could improve the efficiency of execution of futsal-specific movements, ultimately increasing overall futsal performance.…”
Section: Discussionmentioning
confidence: 99%